2010
DOI: 10.1159/000276573
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Choices Regarding Risk-Reducing Surgery in BRCA Mutation Carriers

Abstract: Background/Aims: BRCA mutation carriers have a high lifetime risk of developing breast and ovarian malignancies. As genetic testing becomes widely available, preventative measures are a choice. We evaluated the characteristics of BRCA mutation carriers who chose prophylactic surgery (PS) compared to those who opted for surveillance. Methods: A retrospective chart review of patients with a mutation in the BRCA1 or BRCA2 genes was performed. Results: Ninety women were included, of whom 46 (51%) underwent PS. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Carriers who had a mother or sister with OC were significantly more likely to undergo RRSO (Bradbury et al 2008;Metcalfe et al 2008;Schwartz et al 2003;Uyei et al 2006). Having a personal history of BC was also significantly associated with RRSO (Beattie et al 2009;Kim et al 2013;Metcalfe et al 2008;Schmeler et al 2006;Stuckey et al 2010;Uyei et al 2006). However, in the current study, neither family history of OC nor personal history of BC affected the uptake rate of RRSO.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Carriers who had a mother or sister with OC were significantly more likely to undergo RRSO (Bradbury et al 2008;Metcalfe et al 2008;Schwartz et al 2003;Uyei et al 2006). Having a personal history of BC was also significantly associated with RRSO (Beattie et al 2009;Kim et al 2013;Metcalfe et al 2008;Schmeler et al 2006;Stuckey et al 2010;Uyei et al 2006). However, in the current study, neither family history of OC nor personal history of BC affected the uptake rate of RRSO.…”
Section: Discussionmentioning
confidence: 49%
“…Although inter-center variations, as well as international variations, exist in the uptake rate of RRSO among carriers, Schmeler et al 2006;Stuckey et al 2010). Such variations in uptake rates may arise from differences in the characteristics of the cohorts, selection of study populations, detailed contents of the consultations, and extent of followup periods throughout the studies.…”
Section: Discussionmentioning
confidence: 99%
“…When considering only women with BRCA 1/2 mutation the prevalence of the decisions made are slightly altered. Stuckey et al [20], in a retrospective study of 90 women with BRCA mutation, found that 51% of these women (33% for BRCA 1 mutation carriers and 67% for BRCA 2 mutation) had some kind of prophylactic surgery. Among these, 28% underwent PM and 85% underwent PO.…”
Section: Choosing Prophylactic Mastectomy (Pm)mentioning
confidence: 99%
“…The average age of women who undergo mastectomy interventions was quite variable in the analysed studies; the age range was between 37 and 46 years of age, the majority had children and were married [18][19][20][21][22][23][24][25][26][27][28][29][30]. Women with a history of prior breast cancer are more likely to do prophylactic surgery instead of surveillance (p = 0.003) [20].…”
Section: Choosing Prophylactic Mastectomy (Pm)mentioning
confidence: 99%
See 1 more Smart Citation